DOI: 10.14264/uql.2016.202
|View full text |Cite
|
Sign up to set email alerts
|

Understanding extracellular electron transport of industrial microorganisms and optimization for production application

Abstract: Microbial electrosynthesis (MES) and electro-fermentation are novel approaches to increase microbial production by stimulating the metabolism of the cells electrically. The technique is still in its infancy and while already hyped as promising method to convert CO 2 or cheap carbon sources and electrical energy into valuable chemicals and fuels, little is known about its true potential. This project uses a combination of in silico and in vivo approaches to gather novel information about the benefits and limita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 216 publications
(325 reference statements)
0
6
0
Order By: Relevance
“…For redox stress, it has been shown that degree of reduction of the product spectrum can be much greater than the stoichiometric changes that would be anticipated by simple electron uptake 137 , indicating that electron uptake cannot be the only factor influencing the change in product spectrum. Metaproteomic analysis will be used to analyze the switching mechanisms in both scenarios.…”
Section: Describe the Metabolic Mechanisms Utilized By Mixed Cultmentioning
confidence: 99%
See 4 more Smart Citations
“…For redox stress, it has been shown that degree of reduction of the product spectrum can be much greater than the stoichiometric changes that would be anticipated by simple electron uptake 137 , indicating that electron uptake cannot be the only factor influencing the change in product spectrum. Metaproteomic analysis will be used to analyze the switching mechanisms in both scenarios.…”
Section: Describe the Metabolic Mechanisms Utilized By Mixed Cultmentioning
confidence: 99%
“…This generally refers only to increasing the electron load relative to the substrate rather than providing an electron sink, and has been studied in pure culture fermentations as a means to increase the production of reduced products 123,124,137 . Electron transfer can be accomplished through direct electron transfer via bionanowires, or through indirect electron transfer via electrode-generated hydrogen or using a mediating compound of known redox potential (Section 1.3.3).…”
Section: Redox Stress From Exogenous Electron Mediators Not Electronmentioning
confidence: 99%
See 3 more Smart Citations